Uji Aktivitas Antiinflamasi Ekstrak Etanol Daun Tumbuhan Akar Kaik-Kaik (Uncaria cordata (Lour.) Merr) Terhadap Tikus Putih (Rattus norvegicus) Jantan - Tri Nova Lovena; Rahmawati, Noveri (Fakultas MIPA dan Kesehatan, Universitas Muhammadiyah Riau, 2022)
The study has been carried out of antiinflammatory activity of ethanol extract leaves of plant akar kaik-kaik (Uncaria cordata (Lour.) Merr of the male white rat (Rattus norvegicus). The ethanol extract was first conducted quality checks extracts include: organoleptic test, Thin Layer Chromatography profiles (TLC), determination of water content, drying shrinkage, and ash content. The results showed the ethanol extract the requirements extracts in general. Further test antiinflammatory activity of the white rat (Rattus norvegicus) males using the paw edema. Animal trials were divided into 5 groups: negative control group Na CMC 1%, a positive control diclofenac sodium 4.5 mg/kg weight of the rat and the ethanol extract dose of 100, 200, and 400 mg/kg weight of the rat, the rats are challenged by a subcutaneous injection of 1% solution of carrageenan into the plantar side of the left hind paw, result showed that the ethanol extract doses of 100, 200 and 400 mg/kg weight of the rat had a significantly antiinflammatory activity (p <0.05).